Case series of rash associated with influenza B in school children. Issue 1 (10th November 2014) - Skowronski, Danuta M.; Chambers, Catharine; Osei, William; Walker, Jill; Petric, Martin; Naus, Monika; Li, Yan; Krajden, Mel
<x xml:space="preserve">Abstract</x> This case series describes morbilliform and other rash presentations among schoolchildren during a March 2014 outbreak of influenza‐like illness (ILI) in British Columbia, Canada. Multiplex nucleic acid testing of nasopharyngeal specimens and paired serologic investigations identified that influenza B, characterized as B/Massachusetts/02/2012‐like (Yamagata‐lineage), was the only viral aetiology and most likely cause of ILI and rash. An association between influenza B and rash has been described infrequently elsewhere, and not previously in North America. Influenza B should be considered in the differential diagnosis of febrile exanthem. Evaluation of the nature, incidence and contributing agent–host–environment interactions, and immunologic mechanisms to possibly explain influenza‐associated rash is warranted.